Estimating the public cost of student loans - Claire Crawford; Rowena Crawford; Wenchao Jin (Institute for Fiscal Studies (IFS), 2014)
The UK is currently experiencing a period of considerable fiscal austerity. This has had profound implications for virtually all areas of public spending, including spending on higher education. In this report, we use our own model of graduate earnings and repayments to produce an independent estimate of the long-run cost of providing student loans and we describe how this varies across the graduate earnings distribution. We also quantify some of the uncertainty around these estimates and illustrate the impact of potential changes to the terms under which student loans are offered.
Keywords: 330